The Influence of Facilities, Quality, and Price on Consumer Satisfaction at Welijo Cafe and Freshmarket - Siti Kholifah; Muhamad Imam Syairozi; Abid Muhtarom (Jurnal Multidisiplin Sahombu, 2024)
This study aims to examine the influence of facilities, quality, and price on consumer satisfaction at welijo cafe and freshmarket. This study used a sample of 97 respondents. The hypothesis test used in this study uses validity test, reliability test, classical assumption test, determination coefficient test, multiple linear regression test, t test, and f test. The data that has been collected is analyzed using SPSS version 25. The results of the t-test analysis showed that the facility variable (X1), the quality variable (X2), and the price variable (X3) had a positive influence on consumer satisfaction (Y). With the result of (X1) t count (3,054) > t table (1,985), (X2) t count (3,846) > t table (1,985), (X3) t count (2,603) > t table (1,985). The results of the F test were obtained with an F value calculated > F table (68,342 > 2.70). The test results show that facilities, quality, and price partially affect consumer satisfaction at welijo cafe and freshmarket, the results of simultaneous testing of facilities, quality, and price affect consumer satisfaction at welijo cafe and freshmarket. And the dominant variable that affects consumer satisfaction is quality.